2018
DOI: 10.1371/journal.pone.0198384
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa displays a dormancy phenotype during long-term survival in water

Abstract: Pseudomonas aeruginosa is capable of long-term survival in water, which may serve as a reservoir for infection. Although viable cell counts of PAO1 incubated in water remain stable throughout 8 weeks, LIVE/DEAD staining indicated a high proportion of cells stained with propidium iodide (PI). The proportion of PI-stained cells increased by 4 weeks, then decreased again by 8 weeks, suggesting an adaptive response. This was also evident in an observed shift in cell morphology from a rod to a coccoid shape after 8… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…Propidium iodide is a membrane impermeant intercalator DNA that only stains cells with compromised membrane integrity, presenting with the reddish coloration (LEWENZA et al, 2018;ROCHA et al, 2019). Our data shows the intensity of the reddish color in the first 6 h of STEC in contact with the enterocins (Figure 2); therefore, indicating the penetration of PI.…”
Section: Resultsmentioning
confidence: 68%
“…Propidium iodide is a membrane impermeant intercalator DNA that only stains cells with compromised membrane integrity, presenting with the reddish coloration (LEWENZA et al, 2018;ROCHA et al, 2019). Our data shows the intensity of the reddish color in the first 6 h of STEC in contact with the enterocins (Figure 2); therefore, indicating the penetration of PI.…”
Section: Resultsmentioning
confidence: 68%
“…In fact, the high plasticity of the P. aeruginosa core and accessory genome allows the bacterium to colonize a wide variety of environments, such as soils, water or abiotic surfaces [1–4]. However, P.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of Pseudomonas aeruginosa to establish a chronic infection in cystic fibrosis (CF) lungs despite a wide range of stress sources highlights its high adaptability. In fact, the high plasticity of the P. aeruginosa core and accessory genome allows the bacterium to colonize a wide variety of environments, such as soils, water or abiotic surfaces [1][2][3][4]. However, P. aeruginosa adaptive processes have been especially described in the context of pulmonary infections.…”
Section: Introductionmentioning
confidence: 99%
“…A similar experiment incubating P . aeruginosa biofilm in nutrient poor conditions demonstrated a decrease in ATP levels without a loss of viable bacteria [ 68 ]. Consistent with this previous study, we observed that the levels of ATP in the untreated biofilm were lower in the five day DPBS incubated biofilms compared with 24 hour biofilms as determined by BacTiterGlo analysis while the colony forming units (CFUs) were not significantly different ( S8 Fig ).…”
Section: Resultsmentioning
confidence: 99%